Impactos cumulativos na avaliação de impactos ambientais: fundamentação, metodologia, legislação, análise de experiências e formas de abordagem - Oliveira, Valéria Regina Salla de (2008)
Current subjects as the global heating, reduction in n the ozone layer and the loss of the biodiversity, among other, are resulted of centuries of human actions considered without importance by its low prompt significance and whose impacts had not been evaluated. Although the evaluation of environmental impacts - EIA the to have been instituted more than thirty years, its practical one more common it is in the project level and it is not common to evaluation of these impacts, called of cumulative impacts - IC. The need of the consideration of these impacts made a process that considered them to appear - the Cumulative Impact Assessment - CIA. CIA has been studied, practiced and argued at several countries, however in Brazil, its practice is not common. Although the legislation approaches the consideration of cumulative impacts, they don't know each other approaches and methodologies adapted for such analysis, nor as to consider IC in the process of environmental licensing. With base in this gap, this work had as aim to do a conceptual theoretical survey on cumulative impacts and its analysis process, identifying in the literature the conceptual framework, tools, methodologies, application forms and case studies. After the critical analysis of the data, it was traced a conceptual, theoretical and technical profile and presented as result proposed and recommendations for subsidy to a possible systematization of the procedures; aimed the application difficulties and adaptation needs so that the practice of AIC in Brazil is implanted, as well as in several countries.